UNESCO World Heritage Site Designation: Transforming Tourism Spaces. A Site Communtty’s Perspective - George, E. Wanda (Turyzm/Tourism, 2008)
Often, a catalyst emerges as a stimulating force behind rapid tourism development. This catalyst frequently takes shape as an unusual occurrence. event or attraction, and becomes a trigger for vigorous political and economic development activity to transform new spaces for tourism. In one small rural community in Nova Scotia, Canada, this catalyst was its designation in 1995 as UNESCO World Heritage Site. This article presents research that examined residents' attitudes and perceptions about their UNESCO designation, tourism development, impacts and change in the community ten years after the prestigious award.